ON HYPERSPACES OF SOFT SETS - Metin Aktağ; Fethullah Erol (Journal of New Theory)
– In this paper first, we introduce the soft sets families( ), ( ) and we investigate basic properties of them. Second, by use these soft families, we introduce some hyperspaces of soft sets, called upper (lower) and Vietoris soft topological space, which defined on classes of soft sets define the upper and lower Vietoris continuity of soft multifunction and we give the relationship between Vietoris continuity of soft multifunction and continuity of soft mapping